Multi-solid waste composite rapid solidification iron-containing briquette and preparation method thereof

CN122959515APending Publication Date: 2026-10-23GUANGXI LIUGANG ENVIRONMENTAL PROTECTION CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611148096.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

该方法采用水溶性羧甲基纤维素钠、工业废液组成的有机粘结剂搭配氯化镁与复合使用,粘结剂用量至少3%,粘结剂用量高,且有机粘结剂高温下容易失效,导致入炉过程中粉化严重,造成扬尘增加除尘压力

Benefits of technology

[0024]本发明成型体系利用氯化盐电离产生氯离子,破除氧含铁物料表面钝化膜,溶出二价铁离子;水分蒸发过程中氯盐析出针状晶体形成初级粘结骨架;液相中二价铁氧化生成纳米氢氧化铁胶体,形成二级胶凝骨架,二者协同赋予压块机械强度,仅依靠空气自然供氧时,压块内部氧化不足、易产生膨胀微裂纹,而氧化剂在压块内部原位提供活性氧,提升氢氧化铁胶体生成量,从而提高压块的固结速率,降低压块的养护时间;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of multi-solid waste composite rapid curing iron-containing briquette and preparation method thereof, belong to metallurgical iron-containing solid waste resource utilization technical field.The iron-containing briquette includes the following weight fraction components: composite iron-containing base material 100 parts, chloride salt binder 0.2-0.6 parts, oxidizing agent 0.3-2.0 parts, conductive reinforcing additive 0-0.3 parts, water 3-6 parts.The iron-containing briquette is premixed to obtain premix by composite iron-containing base material, conductive reinforcing additive and oxidizing agent, then chloride salt binder aqueous solution is sprayed on the premix, and mixed material is obtained by stirring, after the mixed material is laid in the forming mold, low-pressure pre-pressing is carried out first, then high-pressure steady pressure vibration forming is carried out, and after demolding, film coating airtight curing is obtained to obtain iron-containing briquette.The application uses chloride salt binder and oxidizing agent synergistic effect, which can accelerate iron corrosion, the amount of binder is small, and the iron grade is not reduced, and the prepared iron-containing briquette can be used to replace scrap steel for converter steelmaking.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metallurgical iron-containing solid waste resource utilization technology, specifically to a multi-solid waste composite rapid solidification iron-containing briquettes and its preparation method. Background Technology

[0002] Currently, the common route for steel mills in the industry to process iron-containing solid wastes such as slag steel, blast furnace slag magnetic separation iron particles, steel slag magnetic separation powder, iron oxide scale, and converter dust is mainly to replace scrap steel with briquettes for recycling in the converter. The conventional processes are mainly hot pressing and cold pressing.

[0003] Hot pressing (hot melt pressing) is a process that uses iron particles, machining iron filings, and iron-containing crushed materials as main raw materials. It employs hot melt heating technology and pressure processing equipment to press the material into shape in a mold. External gas / electric heating is used to heat the iron-containing materials to 600℃~900℃. Under pressure, the materials self-bond and form by melting their own iron oxides at high temperatures, ultimately resulting in cylindrical scrap steel products with specific dimensions and weight, and a surface free of grease and impurities. The hot pressing process requires a TFe content of ≥86.0% and has extremely strict requirements for the raw materials used. The raw materials used in the hot pressing process must be iron particles, machining iron filings, and iron-containing crushed materials. Oily filings with high oil content are prohibited. The process must not mix with iron oxide scale, oxygen cutting slag, non-standard steel balls, pig iron powder, mineral powder, or metal processing crushed scrap steel with excessive composition (which is not accepted). Mixing with calcined iron is also prohibited. The hot pressing process has stringent requirements for material particle size and moisture content. Converter dust, due to its small particle size, is prone to coking and pipe blockage if directly fed into the furnace, requiring pre-drying and granulation. Due to differences in thermal conductivity, iron and steel particles have insufficient fusion bonding interfaces, leading to easy delamination and cracking of the pressed briquettes. This makes it impossible to co-process other iron-containing solid wastes within the steel plant, limiting production to a single type of material and resulting in low overall efficiency in the comprehensive disposal of iron-containing solid wastes. Furthermore, elemental iron and low-valence iron oxides in the raw materials rapidly oxidize to high-valence iron oxides in an oxygen-rich environment above 600℃, resulting in a 3%–7% iron loss per ton of pressed briquettes. This significantly reduces the effective iron grade entering the furnace, ultimately leading to a decrease in metal yield during steelmaking. Finally, the hot pressing process relies on high-temperature forming, resulting in high energy consumption and a high risk of exceeding carbon emission standards. Moreover, the entire production line requires drying, heating furnaces, a high-temperature pressing unit, and a flue gas cooling system, leading to large equipment investment and high maintenance and material costs.

[0004] Currently, to avoid the high energy consumption and high pollution problems of hot pressing, the industry is gradually promoting room temperature cold pressing (cold pressing briquettes). Traditional cold pressing mainly produces cold-pressed blocks or pellets. Cold-pressed blocks typically use machined iron filings (shavings) and steel scrap as raw materials, which are pressed into shape in molds at room temperature using pressure processing equipment to obtain cylindrical scrap steel products with specific dimensions and weights, and a surface free of grease and impurities. The product shape is briquettes or cylinders. This cold pressing process has high requirements for raw materials and cannot achieve integrated treatment of multiple types of iron-containing solid waste, resulting in low comprehensive utilization of solid waste. Cold-pressed pellets, on the other hand, use iron-containing powder as raw material, add a certain amount of binder, and are pressed into pellets using a high-pressure briquetting machine. Cold-pressed pellets can be naturally cured or dried and sent to steelmaking as slag-forming agents. Because the raw materials lack binding properties, the amount of binder used is high, resulting in a decrease in the total iron content of the cold-pressed pellets and an increase in steel slag production.

[0005] For example, Chinese invention patent CN 106544456 A discloses a method for producing converter cold-pressed briquettes using blast furnace slag iron. The method uses blast furnace slag iron, gas mud or gas ash, and iron oxide scale as raw materials, mixed with a binder. The mixture is first ground in a mixing mill for 15-25 minutes until homogeneous, then pressed into shape using a cold-pressing machine, and naturally cured outdoors with water for 10-48 hours to complete the preparation. The mass percentages of the components used to prepare the cold-pressed briquettes are as follows: 30-60 parts blast furnace slag iron, 20-30 parts gas mud or gas ash, 20-50 parts iron oxide scale, and 8-17 parts binder. The binder is composed of 4-7 parts bentonite, 3-6 parts water glass, and 2-4 parts halogen powder. This method uses bentonite, water glass, and halogen powder as an inorganic composite binder system. Bentonite, as a traditional inorganic binder, provides initial plastic bonding force and green strength; water glass (sodium silicate) acts as a reinforcing agent or auxiliary binder, improving the cold mechanical strength and certain thermal stability of the pellets; halogen powder (chloride salt) mainly promotes rapid consolidation, improves early strength, and shortens the curing cycle. Although the inorganic composite binder system of halogen powder, bentonite, and water glass can accelerate curing and reduce curing time, the dosage of this inorganic composite binder system is high, at least 8%, and the use of inorganic binders such as bentonite and water glass is costly. It also reduces the total iron content of the finished product, resulting in an increase in steel slag. Furthermore, the introduction of water glass as a binder inevitably introduces silica, leading to an increase in silica content. Since the converter steelmaking process requires desiliconization, there are strict restrictions on the SiO2 content of the raw materials entering the furnace. The introduction of SiO2 not only increases the metallurgical load of converter desiliconization and the consumption of slag-forming materials, but also leads to increased slag volume and iron loss.

[0006] For example, Chinese invention patent CN 104775023 A discloses a method for producing cold-pressed pellets for steelmaking. The production process includes the following steps: (1) pre-mixing steelmaking secondary dust, converter mud, and iron oxide scale in a weight ratio of (20~23):(55~65):(10~20) and stirring evenly to form a mixture; (2) preparing a binder by mixing water-soluble sodium carboxymethyl cellulose and industrial waste liquid in a weight ratio of 1:(15~50); (3) preparing a magnesium chloride solution by mixing magnesium chloride hexahydrate and water in a weight ratio of 1:1; (4) adding 3%~5% binder and 0.5%~1.5% binder to the mixture. The magnesium chloride solution is mixed with a roller mill for 100-150 seconds to form pellets; (5) the pellets are injected into a briquetting machine and cold-pressed into pellets with a diameter of 45-55mm × 30-40mm × 20-30mm, and then naturally piled up to dry. This method uses an organic binder composed of water-soluble sodium carboxymethyl cellulose and industrial waste liquid in combination with magnesium chloride. The binder dosage is at least 3%, and the high binder dosage, coupled with the fact that the organic binder is prone to failure at high temperatures, leads to severe pulverization during the furnace process, resulting in increased dust and dust removal pressure.

[0007] Therefore, the existing cold pressing method, which is a non-bonding system, uses a single raw material and cannot co-process multiple solid wastes. In contrast, the system with added binders uses chloride salts in combination with inorganic or organic binders. Although the curing time is short, the amount of binder used is relatively large. Inorganic binders are prone to introducing impurities, leading to increased slag and iron loss, while organic binders pulverize at high temperatures.

[0008] Therefore, in view of the multiple inherent defects of the hot pressing process and the traditional cold pressing process, there is an urgent need to develop a multi-solid waste composite rapid solidification iron-containing briquettes and its preparation method, which can synergistically treat a variety of iron-containing solid wastes, has a short curing cycle, high iron content, and does not introduce harmful components such as silicon, sulfur, and phosphorus, and does not increase the amount of steel slag. Summary of the Invention

[0009] To address the aforementioned problems, the present invention aims to provide a multi-solid waste composite iron-containing briquette and its short-cycle room-temperature curing preparation method. By combining a chloride salt binder with an oxidant, it can not only synergistically treat multiple iron-containing solid wastes, but also has the advantages of short curing cycle and high iron content.

[0010] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: a multi-solid waste composite rapid solidification iron-containing briquette, comprising the following weight proportions:

[0011] The composite iron-containing base material consists of 100 parts, chloride salt binder of 0.2 to 0.6 parts, oxidant of 0.3 to 2.0 parts, conductive reinforcing agent of 0 to 0.3 parts, and water of 3 to 6 parts.

[0012] Preferably, the composite iron-containing base material is at least two of the following: blast furnace slag magnetic separation iron particles, steel slag magnetic separation powder water-washed ball mill steel particles, oxygen cutting slag, iron oxide scale, and converter dust with a total iron content of ≥50%.

[0013] Preferably, the chloride salt binder is one or more of magnesium chloride hexahydrate, anhydrous magnesium chloride, calcium chloride, ferric chloride, and industrial sodium chloride.

[0014] Preferably, the oxidant is one or more of iron oxide red, manganese dioxide, hydrogen peroxide, and potassium permanganate.

[0015] Preferably, the conductivity-enhancing agent is ultrafine flake graphite powder with a D50 ≤ 5 μm.

[0016] This invention also provides a method for preparing the above-mentioned multi-solid waste composite rapid solidification iron-containing briquettes, comprising the following steps:

[0017] S1. Dissolve the chloride salt binder in water to obtain a chloride salt aqueous solution. Add the composite iron-containing base material to the mixer, add the conductive reinforcing agent and oxidant, mix and stir evenly to obtain a premix. Then spray the chloride salt aqueous solution onto the premix and continue stirring until the material can be formed into a ball by hand and disperses when dropped to the ground to obtain a mixture.

[0018] S2. After the mixture is placed in the molding die, it is fed into the hydraulic vibration cold pressing molding machine. First, low-pressure pre-pressing and degassing are performed, and then high-pressure stable vibration molding is performed. After demolding, a single wet blank is obtained.

[0019] S3. Stack the demolded wet blanks, cover them with film and seal them. Cur them for 1-3 days at an ambient temperature of 25-38℃ and a humidity of 80%-95% to obtain the finished iron-containing briquettes.

[0020] Preferably, the pre-compression pressure of the low-pressure pre-compression exhaust is 3 MPa, and the pre-compression time is 1 s.

[0021] Preferably, the high-pressure stabilizing vibration molding has an excitation frequency of 50-80Hz, an amplitude of 1.0-1.2mm, a molding pressure of 12-18MPa, and a holding time of 2-4s.

[0022] Preferably, the iron-containing block is a cylinder with a diameter of 200 mm and a thickness of 60-100 mm.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The molding system of this invention utilizes the ionization of chloride salts to generate chloride ions, which break the passivation film on the surface of oxygen-containing iron materials and dissolve ferrous ions. During the evaporation of water, chloride salts precipitate needle-like crystals to form a primary bonding skeleton. In the liquid phase, ferrous ions are oxidized to generate nano-ferric hydroxide colloids, forming a secondary gelling skeleton. The two work together to give the briquettes mechanical strength. When relying solely on natural oxygen supply from the air, the internal oxidation of the briquettes is insufficient and expansion microcracks are easily generated. However, the oxidant provides active oxygen in situ inside the briquettes, increasing the amount of ferric hydroxide colloids generated, thereby increasing the consolidation rate of the briquettes and reducing the curing time.

[0025] This invention relates to iron-containing briquettes. By adding conductive reinforcing agents, graphite, relying on its layered crystal structure, acts as a solid lubricant. The high-pressure vibration molding process reduces internal friction between iron-containing materials, improves the overall density uniformity of the briquettes, eliminates internal delamination defects, and reduces wear on the inner wall of the cylindrical mold, extending its service life. Flake graphite overlaps within the billet, optimizing the pore channel structure, balancing oxygen permeation rates, and alleviating the problems of premature surface hardening and insufficient oxygen supply to the core in thick-sized circular briquettes. The graphite flakes can absorb the volume expansion stress caused by ferrous oxidation, inhibiting the initiation of internal microcracks during the curing stage. When the briquettes are fed into the metallurgical furnace for smelting, the flake graphite acts as an internal reducing agent, improving smelting conditions, assisting slag formation, and reducing the consumption of supplementary heat exchangers. Simultaneously, it can construct micro-galvanic cells within the system, improving the conductivity of the briquettes and building a global electron conduction network in the billet, making electron transfer and ion migration smoother, eliminating the difference in curing rates between the surface and core of traditional briquettes, and synergistically increasing the corrosion rate with oxidants, further shortening the overall curing cycle by more than 60%.

[0026] The present invention first performs low-pressure pre-pressing to expel air from the interior of the blank, and then performs high-pressure stabilizing and agitation molding to improve density, thereby eliminating air holes and delamination defects in the briquettes and further improving drop strength and compressive strength. Detailed Implementation

[0027] The specific embodiments of the present invention will be further described below with reference to examples.

[0028] The material specifications used in the following examples are as follows:

[0029] The composite iron-containing matrix material is selected from granules or powders, with the particle size of the granules being 0.1 to 3 mm; the ultrafine flake graphite powder is selected with a particle size of D50 ≤ 5 μm.

[0030] Example

[0031] The preparation method of iron-containing briquettes includes the following preparation steps;

[0032] S1. Dissolve the chloride salt binder in water at room temperature to obtain a chloride salt aqueous solution. Add the composite iron-containing base material into the mixer according to the formula (see Table 1), add the conductive reinforcing agent and oxidant (30% hydrogen peroxide is added by spraying), mix and stir evenly to obtain a premix. Then spray the chloride salt aqueous solution onto the premix and continue stirring until the material can be formed into a ball by hand and disperses when dropped to obtain a mixture.

[0033] S2. After the mixture is placed in the molding die, it is fed into the hydraulic vibration cold pressing molding machine. First, low-pressure pre-pressing and venting are performed. The pre-pressing pressure is 3MPa and the pre-pressing time is 1s. Then, high-pressure stable vibration molding is performed. The vibration frequency is 75Hz, the amplitude is 1.2mm, the molding pressure is 18MPa, and the holding time is 4s. After molding, hydraulic synchronous ejection and demolding are performed. The demolding speed is 0.12m / s to obtain a single wet blank. A circular mold is selected for the molding die. The mold diameter is 200mm, and the mold thickness is 60mm or 100mm. The mold thickness is selected according to the thickness of the finished product (the finished product thickness of each embodiment and comparative example is shown in Table 1).

[0034] S3. Stack the demolded single wet blanks, cover them with film and seal them, and cure them for 1-3 days at an ambient temperature of 28℃ and humidity of 90% (see Table 2 for the curing days of each embodiment) to obtain the finished iron-containing briquettes.

[0035] Table 1 shows the weight percentages of each component, the thickness of the finished product, and the curing time in Comparative Example 1 and Examples 1-8.

[0036] Table 1. Weight proportions of each component, finished product thickness, and curing time of iron-containing briquettes.

[0037]

[0038] The iron-containing briquettes of this invention, after curing for 1-3 days, achieve a compressive strength that meets the requirements for converter steelmaking entry strength (>3000N). In contrast, in Comparative Example 1, without the addition of an oxidant, the iron-containing briquettes required curing for up to 10 days before their compressive strength met the converter steelmaking entry strength requirements. This indicates that adding an oxidant accelerates the solidification of the iron-containing briquettes, reduces curing time, and the curing time can be further reduced with increasing oxidant dosage.

[0039] The molding system of this invention relies on chloride ions generated by the ionization of chloride salts to break the passivation film on the surface of iron-containing materials and dissolve ferrous ions. The primary bonding skeleton is formed by the precipitation of needle-like crystals by chloride salts, and the secondary cementing skeleton is formed by the oxidation of ferrous ions in the liquid phase to generate nano-ferric hydroxide colloids. The two-phase synergy gives the briquettes overall mechanical strength. By adding an oxidant, oxygen can be replenished in situ inside the green body, which greatly increases the amount of ferric hydroxide colloid generated, solves the problem of insufficient oxidation and microcrack expansion defects caused by insufficient natural oxygen supply, and significantly accelerates the consolidation rate and shortens the curing cycle. Simultaneously, ultrafine flake graphite is added as a conductivity enhancer and structure regulator. Its layered structure can exert a solid lubricating effect, reducing internal friction during molding, eliminating layering defects within the billet, improving the density uniformity of the billet, and reducing mold wear. The overlapping of graphite flakes can optimize internal pore channels and balance oxygen permeation rate, effectively improving the problem of rapid surface hardening and uneven oxygen supply in the core of thick-gauge briquettes. It can also absorb oxidative expansion stress and inhibit the initiation of microcracks. In addition, graphite can construct a full-domain micro-galvanic cell conductive network, smoothly promoting electron transfer and ion migration, eliminating the solidification difference between the surface and the interior of the billet, and forming a highly efficient synergistic system with oxidants. This significantly improves the chloride corrosion consolidation efficiency and can shorten the overall curing cycle by more than 60%. Furthermore, when the finished briquettes are put into the furnace for smelting, graphite can act as an internal reducing agent, optimizing smelting conditions, assisting slag formation, and reducing the consumption of heat-generating agents.

[0040] The above description is a detailed description of the preferred embodiments of the present invention. However, the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modifications made under the technical spirit of the present invention should be covered by the patent of the present invention.

Claims

1. A multi-solid waste composite rapid solidification iron-containing briquettes, characterized in that, Includes the following weight array: The composite iron-containing base material consists of 100 parts, chloride salt binder of 0.2 to 0.6 parts, oxidant of 0.3 to 2.0 parts, conductive reinforcing agent of 0 to 0.3 parts, and water of 3 to 6 parts.

2. The multi-solid waste composite rapid solidification iron-containing briquettes as described in claim 1, characterized in that, The composite iron-containing base material is at least two of the following: blast furnace slag magnetic separation iron particles, steel slag magnetic separation powder water-washed ball mill steel particles, oxygen cutting slag, iron oxide scale, and converter dust with a total iron content ≥50%.

3. The multi-solid waste composite rapid solidification iron-containing briquettes as described in claim 1, characterized in that, The chloride salt binder is one or more of magnesium chloride hexahydrate, anhydrous magnesium chloride, calcium chloride, ferric chloride, and industrial sodium chloride.

4. The multi-solid waste composite rapid solidification iron-containing briquettes as described in claim 1, characterized in that, The oxidant is one or more of iron oxide red, manganese dioxide, hydrogen peroxide, and potassium permanganate.

5. The multi-solid waste composite rapid solidification iron-containing briquettes as described in claim 1, characterized in that, The conductivity enhancement agent is ultrafine flake graphite powder with a D50 ≤ 5 μm.

6. A method for preparing multi-solid waste composite rapid solidification iron-containing briquettes as described in any one of claims 1-5, characterized in that, Includes the following steps: S1. Dissolve the chloride salt binder in water to obtain a chloride salt aqueous solution. Add the composite iron-containing base material to the mixer, add the conductive reinforcing agent and oxidant, mix and stir evenly to obtain a premix. Then spray the chloride salt aqueous solution onto the premix and continue stirring until the material can be formed into a ball by hand and disperses when dropped to the ground to obtain a mixture. S2. After the mixture is placed in the molding die, it is fed into the hydraulic vibration cold pressing molding machine. First, low-pressure pre-pressing and degassing are performed, and then high-pressure stable vibration molding is performed. After demolding, a single wet blank is obtained. S3. Stack the demolded wet blanks, cover them with film and seal them. Cur them for 1-3 days at an ambient temperature of 25-38℃ and a humidity of 80%-95% to obtain the finished iron-containing briquettes.

7. A method for preparing a multi-solid waste composite rapid solidification iron-containing briquettes as described in claim 6, characterized in that, In step S2, the pre-pressure of the low-pressure pre-pressure exhaust is 3MPa, and the pre-pressure time is 1s.

8. A method for preparing a multi-solid waste composite rapid solidification iron-containing briquettes as described in claim 6, characterized in that, In step S2, the excitation frequency of the high-pressure stabilizing vibration molding is 50-80Hz, the amplitude is 1.0-1.2mm, the molding pressure is 12-18MPa, and the holding time is 2-4s.

9. A method for preparing a multi-solid waste composite rapid solidification iron-containing briquettes as described in claim 6, characterized in that, The iron-containing press block is a cylinder with a diameter of 200 mm and a thickness of 60-100 mm.

Citation Information

Patent Citations

  • Manufacturing method for cold-pressed pellets for steelmaking

    CN104775023A

  • Method for producing cold-pressed block for converter by utilizing iron in blast-furnace slag

    CN106544456A